Plunkett Foundation - Technical Centre for Agricultural and Rural Cooperation (Technical Centre for Agricultural and Rural Cooperation, 1992)
The Plunkett Foundation provides a wide range of services in support of the sustainable development of new and established people-centred businesses, particularly cooperative enterprises and farmer controlled organizations. Its aims are to improve...